2(5)-3y=9

Simple and best practice solution for 2(5)-3y=9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(5)-3y=9 equation:


Simplifying
2(5) + -3y = 9

Multiply 2 * 5
10 + -3y = 9

Solving
10 + -3y = 9

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -3y = 9 + -10

Combine like terms: 10 + -10 = 0
0 + -3y = 9 + -10
-3y = 9 + -10

Combine like terms: 9 + -10 = -1
-3y = -1

Divide each side by '-3'.
y = 0.3333333333

Simplifying
y = 0.3333333333

See similar equations:

| 2x-3y=y | | 2x-3y=p | | 30=-16t^2+130t+90 | | 3x+22+2x+88=60 | | 3-5f-7-3f=9 | | 7x+1y+2z=46 | | 3p(p+5)4(p-7)= | | 2x+88+3x+22=60 | | 10=-16t^2+150+50 | | 6p+5=29 | | 14175=x+x(0.135) | | 10t=-16t^2+150t+50 | | x^2-2mx+m=0 | | 10t=-16t^2+150t+60 | | 2x+67+3x+133=75 | | 5(x+3m+4)= | | 55-0.5x=30 | | 2x+46+3x+29=85 | | 4(2x-8)-6(x-4)=2 | | -5(x+6)+5= | | 3x+2+-1=x+6+-1 | | 2(x-8)=62 | | c-0.25c=120 | | (17b-6)-8(2b+1)=7 | | c-3.25c=120 | | -6(5x+4)+5= | | 4cosx^2-2=0 | | cosx^2=0 | | 3.2-(-2.3)=3.2+2.3 | | 49t^3-49t=0 | | 3(1.2x-0.2)=6.6 | | 6x-3+10x=2 |

Equations solver categories